Audio app using MATLAB app designer (III) - Nazri Bin Surin (Nanyang Technological University, 2024)
This project presents the development of a MATLAB audio app aimed at enhancing audio signal processing. Leveraging MATLAB's Digital Signal Processing (DSP) capabilities, the prototype successfully addressed limitations in real-time signal processing, enabling real-time simulation for non-linear and time-varying signals. Key features include the app's ability to facilitate real-time simulation for user-provided audio or video files and the incorporation of a diverse library of signals including deterministic signals, singularity signals, communication signals, sounds of oceans and cosmos, sounds of number sequences and sounds of constants. Throughout the project, various discoveries were made, leading to innovative solutions such as utilizing the pan and zoom feature, adjusting panel stacking order and implementing dropdown menus, which effectively addressed challenges encountered during development. Additionally, enhancements to visual appeal and usability underscored the iterative nature of development.